Incentives Compatible Constraints Pada Pembiayaan Mudharabah Bank Nagari Syariah - Yeni Oktaviani (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2017)
The realization of mudharabah financing in sharia banks is low than murabahah financing due to the high risk of moral hazard. This study proves that moral hazard risk of mudharabah financing can be reduced by incentive compatible constraints as risk mitigation. The findings of this study indicate that high moral hazard risk in mudharabah financing in Bank Nagari Shariah can be reduced by establishing several covenants at the beginning of the contract. Incentive compatible constraints were introduced by John R. Pressley and Session as the asymmetric risk mitigation of moral hazard information. The Nagari Bank Shariah identifies the moral hazard risk caused by internal and external factors of the bank, so that risk mitigation is also done internally and externally. Incentive compatible constraints as a mitigation of moral hazard risk and effective to reduce the occurrence of moral hazard risk for cooperative and institutional customers. The data mining process uses structured interviews with financing analysts and sharia risk management team of Bank Nagari Syariah. Documentation of bank financial statements, implementation guidelines of sharia financing and sustainability report 2014. The data obtained then analyzed by qualitative approach. Data analysis technique is done descriptively qualitative with incentive compatible constraints as an analytical tool.